Have a Personal Vehicle: Really Need or Simply Want? - Hasim, Abdul Hafid; Said, Lambang Basri; Hafram, Maryam (International Journal of Environment, Engineering & Education, 2019)
The more and more efficiently the community in owning and determining vehicle choices has resulted in increasingly increasing the trend of private vehicle use as the primary transportation mode replacing public transportation. Planned Behavior Theory is expected to accurately predict people's intentions and behavior in using private vehicles. The variables used are the independent variable Attitude Toward, Subjective Norm and Perceived Behavioral Control, then Intention Behavior as the intervening and Behavior dependent variable. The research population is the community of private motorists using cars and motorbikes in the city of Makassar. The number of samples used was 210 respondents. The sampling used is Purposive Random Sampling. Primary data and information through an open questionnaire. Analysis of research data with the Structural Equation Model with IBM AMOS Software. The results obtained show that attitude toward intention to behavior means that attitude variables compared to Subjective Norm and Perceived Behavioral Control variables predominantly affect Intention and Behavior. The Attitude Toward of vehicle users who are influenced by Behavior belief will ensure that the vehicles they use can make social values increase, will be more valued and respected. Vehicles are not only a means of transportation but also a symbol of a person's establishment.